Predicting uptake of continuous positive airway pressure (CPAP) therapy in obstructive sleep apnoea (OSA): A belief-based theoretical approach - Skinner, T.; McNeil, L.; Olaithe, M.; Eastwood, Peter; Hillman, D.; Phang, J.; De Regt, T.; Bucks, R. (2013)
Purpose: Obstructive sleep apnoea (OSA) is a common disorder, for which continuous positive airway pressure (CPAP) therapy is a standard treatment. Despite its well-established efficacy, many patients choose not to initiate CPAP treatment. The present study investigated the degree to which biological measures (e.g. Apnoea-Hypopnoea Index [AHI]), symptom experiences (e.g. fatigue) and illness representations (e.g. perceived consequences) predict the decision of individuals newly diagnosed with OSA to undergo a trial of CPAP therapy. Methods: Four hundred forty-nine individuals (316 males) newly diagnosed with OSA. Epworth sleepiness scale (ESS), Fatigue Severity Scale, Depression Anxiety Stress Scale and Illness Perception Questionnaire-Revised (IPQ-R) were administered at time of sleep study. These, patient demographics and sleep study variables were used to determine factors predicting patient decision to proceed with a trial of CPAP. Results: The participants were most likely to attribute their OSA to unchangeable and psychological factors. For those with moderate OSA (AHI, 15 to 30) IPQ-R illness consequence was predictive of decision to initiate CPAP (p = 0.002). For severe OSA (AHI > 30) age, ESS and IPQ illness causal beliefs were predictive of decision to initiate CPAP (p < 0.001). Conclusions: Illness beliefs are important determinants of the choice of recently diagnosed OSA patients whether or not to undertake a trial of CPAP therapy. Concerns about illness consequences were important in those with moderate OSA. In severe OSA, sleepiness symptoms are more prominent and a more significant determinant of CPAP uptake along with age and causal beliefs. © 2013 Springer-Verlag Berlin Heidelberg.